Contemporary holography - Narayanamurthy, C. S. (Multidisciplinary and applied optics, 2023)
"This book is unique in covering most of developments on optical holography starting from photopolymer recording techniques to CMOS based digital holography. It also covers fundamentals and applications of dynamic holography using photorefractive crystals and many different types of digital holography and its many applications"--